Study on neural stem cell transplantation into natural rat cochlea via round window - Fu, Yong; Wang, Shenqing; Liu, Yingpeng; Wang, Jianting; Wang, Guopeng; Chen, Qingguo; Gong, Shusheng (American journal of otolaryngology, 2009)
The aim of the study is to investigate the survival of neural stem cells (NSCs) in normal rat cochlea and their potential effect on auditory function and cochlea structures via round window transplantation. In comparison with the normal rats without any transplantation (group III), normal rat cochleae were transplanted with NSCs infected with adenovirus carrying green fluorescence protein (GFP) gene (group I) or the artificial perilymph (group II) via round windows. Auditory functions were monitored by thresholds of auditory brain stem responses (ABRs); the cochlea structures were examined by hematoxylin and eosin staining; survivals of implanted NSCs were determined by the expression of GFP; survivals of hair cells were accessed by whole mount preparation; and ultrastructures of hair cells were examined by scanning electron microscopy. There were significant differences in the click-ABR thresholds in rats among all 3 groups neither at pretransplantation nor at posttransplantation; there were no significant differences in these values before and after transplantation in the same rats from each group. After transplantation, the cochlea structures were normal in both group I and group II. Grafted NSCs were visualized by the GFP expression in every turn of the cochlea in all animals of group I. There were no significant differences in the losses of outer hair cells (OHCs) among 3 groups. The inner hair cells and most OHCs were normal in every turns of cochleae of all groups. Neural stem cells survived in normal rat cochlea after transplantation via round window and showed no obvious effects on auditory functions and inner ear pathologic examination of the rat cochlea.